2004
DOI: 10.3748/wjg.v10.i13.1914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of traditional Chinese medicinal enemas on ulcerative colitis of rats

Abstract: AIM:To investigate the effects of traditional Chinese medicinal enema (TCME) on inflammatory and immune response of colonic mucosa of rats with ulcerative colitis (UC), and to observe the pathogenic mechanism. METHODS:Thirty UC rats, induced by intestinal enema together with 2.4-dinitrochlorobenzene (DNCB) and acetic acid, were randomly divided into 3 groups, i.e., GI, GII and GIII. Groups GI and GII were administered with TCME and salazosulfapyridine enema (SASPE), respectively. Group GIII was clystered with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…It has been reported that plant extracts or compounds that show inhibitory effects on these inflammatory cytokines are known to reduce the severity in diseases such as Crohn's disease, multiple sclerosis, RA, etc. [24]. When the profile of cytokine secretion by activated T cells and macrophages were analysed it was revealed that both crude ethyl acetate extract and pure compound of C. mukul significantly suppressed inflammatory cytokines such as IFN, IL-12, TNF-a, IL-1h cytokines (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that plant extracts or compounds that show inhibitory effects on these inflammatory cytokines are known to reduce the severity in diseases such as Crohn's disease, multiple sclerosis, RA, etc. [24]. When the profile of cytokine secretion by activated T cells and macrophages were analysed it was revealed that both crude ethyl acetate extract and pure compound of C. mukul significantly suppressed inflammatory cytokines such as IFN, IL-12, TNF-a, IL-1h cytokines (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a recent survey showed that one-third of both Chinese and Caucasian IBD patients had used complementary and alternative medicines and therapies [4] . Several TCM formulae have been shown to possess an anti-colitic effect in rats [26][27][28] . Recent studies suggest that Scutellariae Radix may have a pharmacological effect against murine colitis [10][11][12] and therefore in this study we aim to further evaluate the therapeutic effect of SRE on DSS-induced rat colitis.…”
Section: Discussionmentioning
confidence: 99%
“…)Improvement of colitis/abolished inflammationImmune-suppressing (reduction of TNFα, IL-12, -17), wound-healing[16]W.chinensis water extractDSS-induced colitisNo datap.o.Improvement of colitis/abolished inflammationImmune-suppressing (suppression of Th1 and Th17 cells)[17]Changtai granulesChronic TNBS-induced colitisDXi.c.Improvement of colitis/abolished inflammationImmune-suppressing (suppression of macrophages/monocytes)[18]G. frondosa water extractTNBS-induced colitis5-ASAp.o.Reversed symptoms of colitisImmune-suppressing (reduction of TNFα, NF-κB and neutrophil influx)[21]Changlu EnemaProtein immunization induced-UCSASPi.c.Reversed inflammatory response (macro- and microscopically)No data[22]Mixed herbal preparationDNCB and acetic acid-induced colitisSASPi.c.Improvement of colitis/abolished inflammationImmune-suppressing (reduction of TNFα, INFγ and IL-6)[23]β,β-demethylacrylshikoninHCT-116 tumor xenograftNonei.p.Reduction of tumor growthinducing apoptosis of tumor cells (increasing level of Bax/ decreasing level of Bcl-2)[41]Shikunshito-KamihoDMH-induced CRCNonein diet (p.o. )Reduction of aberrant crypt fociNo data[42]SophoridineSW480 tumor xenograft5-FUi.p.Reduction of tumor growthinducing apoptosis of tumor cells ( activation of caspase-3 dependent pathways)[45]Spica Prunellae ethanol extractHT-29 tumor xenograftNonep.oReduction of tumor growthinduction apoptosis of tumor cells/inhibition of tumor angiogenesis and proliferation[46]

5-ASA 5-aminosalicylic acid, 5-FU 5-fluorouracil, 6-MP 6-mercaptopurine, CRC colorectal cancer, DMH 1,2-dimethylhydrazine, DNCB 2,4-dinitrochlorobenzene, DS dextran sodium sulfate, DX dexamethasone, i.c.

…”
Section: Treatmentmentioning
confidence: 99%